Effect of heat treatment on fatigue crack growth in IN718/316L multiple-materials layered structures fabricated by laser powder bed fusion. (July 2022) - Duval-Chaneac, M-S; Gao, N; Khan, R.H.U; Giles, M; Georgilas, K; Zhao, X; Reed, P.A.S
Highlights: The effect of heat treatment on multi-layer IN718/316L specimen was observed to cause the appearance of some ductility dip cracking at the interface along with the formation of Laves phases. The mitigation of crack propagation via shielding effect at the interface transition was observed to have a minor effect in comparison to changes in the intrinsic material strength, for stress intensity factor ranges above 20 MPa√m. The effect of HT on IN718 has shown an improvement of its tensile strength by 22%, while on 316L it has shown to decrease its tensile strength by 5.2% due to a recovery from the cellular network . Abstract: Multi-material specimens of 316L stainless steel and IN718 were produced in a layered architecture by the Laser Powder Bed Fusion (L-PBF) process. Specimens were heat treated at temperatures tailored for the combination of 316L and IN718. The effect of the heat treatment on the microstructure and on the tensile properties across the layers was investigated. Two heat-treated bi-layer specimens (No.1 and No.2) and one heat-treated 4-layer specimen (No.3) were tested under 3 point bending fatigue to compare the crack propagation resistance through multiple sets of dissimilar material interfaces. It was found that the crack propagation resistance overall is mainly controlled by the local microstructural strength, while the interface transition is most significant at lower values of stress intensity factor range (ΔK < 20 MPa√m).